2018
DOI: 10.1016/j.conctc.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perceived obstacles to pediatric clinical trial participation: Findings from the clinical trials transformation initiative

Abstract: Enrollment of children into pediatric clinical trials remains challenging. More effective strategies to improve recruitment of children into trials are needed. This study used in-depth qualitative interviews with parents who were approached to enroll their children in a clinical trial in order to gain an understanding of the barriers to pediatric clinical trial participation.Twenty-four parents whose children had been offered the opportunity to participate in a clinical trial were interviewed: 19 whose childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 17 publications
(17 reference statements)
2
44
0
Order By: Relevance
“…, Greenberg et al . ). Measures of parent characteristics, such as familiarity with technology, education and employment, may also help to identify the families for which the intervention is most suitable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Greenberg et al . ). Measures of parent characteristics, such as familiarity with technology, education and employment, may also help to identify the families for which the intervention is most suitable.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, although recruitment via healthcare professionals may offer parents an opportunity to be open about why they opting out, it also opens the risk of gate-keeping and consequent under-recruitment (Sharkey et al 2010, Tromp andVathorst 2015). Future researchers should design methods of recruitment with parent and multidisciplinary team representatives that can provide balanced information about research to all families who fit the criteria from trustworthy sources and capture reasons for opting out , Greenberg et al 2018. Measures of parent characteristics, such as familiarity with technology, education and employment, may also help to identify the families for which the intervention is most suitable.…”
Section: Intervention Feasibility and Implications For Intervention Fmentioning
confidence: 99%
“…Therefore, to increase the consistency of tumor take and growth kinetics, a two-step approach was utilized. Saos2 CDX were first established in female NSG (6)(7)(8) week old mice) by the implantation of 5 × 10 6 Saos2 cells (200 µL 1:1 Matrigel to basal RPMI). We found that matching the gender of the tumor sample with the gender of the NSG mice (6-8 weeks old) used for tumor implant improves tumor take and allows for more consistent tumor growth kinetics.…”
Section: Development Of An Saos2 CDX Model Of Osmentioning
confidence: 99%
“…Additionally, in the last 3-4 decades, early phase clinical trials have failed to show promise for the treatment of not only primary OS, but also the more aggressive (relapsed/refractory) form of the disease [6]. The rarity of this disease and small patient populations continue to pose a challenge for initiating new clinical trials for pediatric and AYA OS patients [7]. Therefore, it is critical to understand the molecular heterogeneity and identify biomarkers within the complex genetic landscape of OS, so that actionable targets can ultimately be tested in clinical trials [3].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials in the neonatal and paediatric critical care setting are challenging to conduct due to ethical and practical considerations [19][20][21][22]. In line with the Medical Research Council's framework for complex intervention development [23] conducting trial feasibility studies can help mitigate these challenges and establish whether the trial is acceptable to parents and practitioners, and practical to conduct [24,25].…”
Section: Introductionmentioning
confidence: 99%